Analysis of Flavor Components of 6 Kinds of Yanshan Chestnut by GC-MS Combined with Electronic Nose/Electronic Tongue - Yin YANG; Jianlan LIANG (Shipin gongye ke-ji, 2024)
The primary objective of this study was to examine the aromatic composition characteristics of six varieties of sugar-roasted 'Yanshan chestnuts' and to discern the distinctions in taste and odor between them. The volatile flavor constituents and pivotal aroma compounds of these sugar-roasted Chinese chestnuts were scrutinized using headspace solid-phase microextraction (HS-SPME) in conjunction with gas chromatography-mass spectrometry (GC-MS) and the odor activity value (OAV) method. Additionally, the volatile odor components and taste were assessed using electronic nose and tongue technologies. Results showed that, a total of 57 compounds were detected via GC-MS in the volatile components of these six types of sugar-roasted Castanea mollissima, which included 19 esters, 12 alcohols, 5 aldehydes, 5 ketones, 4 alkenes, 4 benzodiazepines, 2 amines, and 6 other components. Among these, 23 constituents with an OAV greater than 1 were identified as the key aroma components of the sugar-roasted chestnuts. The electronic nose evaluation illustrated that the predominant volatile odor components of the six sugar-roasted Castanea mollissima were alcohols, aldehydes, ketones, nitrogen oxides, organic sulfides, inorganic sulfides, and methyl groups. Furthermore, the electronic tongue analysis indicated that these six roasted chestnuts exhibited similar taste indices. The richness and umami sensor demonstrated the most substantial response to the different roasted chestnuts, while the sour and astringent tastes were the least prominent. The main taste indices of the roasted chestnuts were determined to be richness, umami, sweetness, saltiness, bitterness, and a lingering bitter aftertaste. The volatile flavor components and their quantities differed among the six types of sugar-roasted chestnuts, implying that the volatile flavor components vary among different sugar-roasted chestnut varieties, and the levels of the same compound also differ between varieties. The use of principal component analysis (PCA), radar chromatogram analysis, and GC-MS technology combined with electronic nose/tongue technologies proved to be an effective means to distinguish the differences in flavor among different varieties of sugar-roasted Chinese chestnuts and identify the key aroma components. This research provides a theoretical foundation for future flavor research on different sugar-roasted Chinese chestnut varieties.